Enhanced green density of binder jetted tungsten heavy alloys with an inorganic metal salt binder - Yuhua Heng; Yiwei Mao; Kunhao Feng; Jianan Zheng; Yingmi Xie; Qingsong Wei (Journal of Materials Research and Technology)
Binder jetting (BJ) possesses considerable potential in forming complex tungsten heavy alloy components. Nonetheless, it is also confronted with challenges such as low green density. Achieving densification typically requires stringent sintering conditions, such as high temperatures or extended durations, which often result in coarse grains and diminished performance in sintered components. This paper introduced a novel inorganic metal salt binder that could generate nanoparticles in situ among the substrate powders. Clearly, the nanoparticles (average size: 360 nm) generated in situ, occupied the interparticle voids between the substrate powders after pretreatment, thereby enhancing the green and pretreated density and reducing the sintering temperature. The pretreated density binder jetted with the novel binder increased by 7.76% compared to that with the commercial binder. Furthermore, surface quality and compressive strength were also improved. The sintered samples could achieve densification at a lower sintering temperature (1500 °C). The increase of capillary force and the elevated solubility of nanoparticles were the primary reasons for densification, which facilitated pore filling and dissolution-reprecipitation during liquid phase sintering, respectively. The ultimate tensile strength, yield strength, and elongation of the sintered samples were 871.06 ± 14.23 MPa, 606.71 ± 9.84 MPa, and 11.00 ± 0.28%, which were 9.50%, 4.30%, and 5.49% higher than those of the sintered samples binder jetted with the commercial binder, respectively. The utilization of inorganic metal salt binders provides a novel approach to the densification and enhancement of the mechanical properties of BJ metallic materials.